2010
DOI: 10.1128/jcm.02045-09
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Virus Inactivation for Studies of Antigenicity and Phenotypic Neuraminidase Inhibitor Resistance Profiling

Abstract: Introduction of a new influenza virus in humans urges quick analysis of its virological and immunological characteristics to determine the impact on public health and to develop protective measures for the human population. At present, however, the necessity of executing pandemic influenza virus research under biosafety level 3 (BSL-3) high-containment conditions severely hampers timely characterization of such viruses. We tested heat, formalin, Triton X-100, and ␤-propiolactone treatments for their potencies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
96
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 38 publications
8
96
0
1
Order By: Relevance
“…The induction of proinflammatory cytokines in response to HPAI H5 infection of human MDMs was inhibited by b-propiolactone-inactivation of the virus [36]. Although this result suggests that replication is required for the induction of proinflammatory cytokines following H5N1 IAV infection of macrophages, b-propiolactone was shown to cause a 16-fold reduction in viral HA activity [61]. Thus, decreased cytokine expression may have resulted from decreased virus attachment/entry rather than from decreased productive replication per se.…”
Section: Iav Replication and Hypercytokinemiamentioning
confidence: 62%
“…The induction of proinflammatory cytokines in response to HPAI H5 infection of human MDMs was inhibited by b-propiolactone-inactivation of the virus [36]. Although this result suggests that replication is required for the induction of proinflammatory cytokines following H5N1 IAV infection of macrophages, b-propiolactone was shown to cause a 16-fold reduction in viral HA activity [61]. Thus, decreased cytokine expression may have resulted from decreased virus attachment/entry rather than from decreased productive replication per se.…”
Section: Iav Replication and Hypercytokinemiamentioning
confidence: 62%
“…In vitro infection assays and western blot analysis showed that in the case of PRRSV the entry-associated domains were indeed preserved after treatment at 37°C and that the virus did not replicate anymore [41]. However, heat-inactivated influenza virus (>55°C) lost hemagglutinin and neuraminidase activity [62].…”
Section: Temperaturementioning
confidence: 99%
“…However, BPL-inactivated influenza showed reduced hemagglutinin and neuraminidase activity [62]. Vaccines based on BPL-inactivated virus against SARS-CoV [64], hematopoietic necrosis virus (HNV) [67] and influenza [65], were able to protect on challenge.…”
Section: Aldrithiol or 22´-dithiodipyridinementioning
confidence: 99%
See 1 more Smart Citation
“…RNA was extracted from the FFPE lower lung tissue using the RNeasy FFPE kit (Qiagen) according to the manufacturer's protocol. Total RNA was eluted in a volume of 50 l. All A(H7N7)-positive RNA extracts were subjected to a semiquantitative RT-PCR targeting the influenza virus matrix gene segment to prevent possible resequencing due to low-copy-number input in the reverse transcription (RT)-PCR (24).…”
Section: Methodsmentioning
confidence: 99%